Case Study Of Smoking Behavior Among Suku Anak Dalam Adolescents In Tanjung Village, Bathin VIII Sub-District, Sarolangun Regency, 2025 - Mizya Sabtheca Simanjuntak; Muhammad Syukri; Kasyani Kasyani; Asparian Asparian; Muhammad Ridwan; Puspita Sari (CV. AFDIFAL MAJU BERKAH, 2025)
Smoking behavior among adolescents is a concerning public health issue, especially in remote indigenous communities such as the Suku Anak Dalam. In their daily lives, smoking has become an ingrained habit and is considered normal.This study aims to understand the smoking behavior of Suku Anak Dalam adolescents in Tanjung Village, Bathin VIII Sub-District, Sarolangun Regency, and to identify the social and cultural factors that influence this behavior.This study employed a qualitative approach. Data were collected through in-depth interviews and participant observation involving seven active-smoking adolescents and nine supporting informants (parents, traditional leaders, and community facilitators). The study found that adolescent smoking behavior is influenced by peer pressure, weak parental supervision, and a social environment that normalizes smoking. Cigarettes are perceived as something ordinary and even a necessity. Parental control is weak and the advice given tends to be inconsistent. Smoking behavior among Suku Anak Dalam adolescents results from the interaction of peer influence, permissive parenting, and the normalization of smoking within their environment. This behavior develops from a young age and continues without adequate supervision from parents or community figures